Deletion of caveolin scaffolding domain alters cancer cell migration. Issue 11 (3rd June 2019) - Okada, Sunaho; Raja, Sadaf A.; Okerblom, Jonathan; Boddu, Aayush; Horikawa, Yousuke; Ray, Supriyo; Okada, Hideshi; Kawamura, Itta; Murofushi, Yoshiteru; Murray, Fiona; Patel, Hemal H.
ABSTRACT: Caveolin-1 (Cav-1) is an integral membrane protein that plays an important role in proliferative and terminally differentiated cells. As a structural component of Caveolae, Cav-1 interacts with signaling molecules via a caveolin scaffolding domain (CSD) regulating cell signaling. Recent reports have shown that Cav-1 is a negative regulator in tumor metastasis. Therefore, we hypothesize that Cav-1 inhibits cell migration through its CSD. HeLa cells were engineered to overexpress Cav-1 (Cav-1 OE), Cav-1 without a functional CSD (∆CSD), or enhanced green fluorescent protein (EGFP) as a control. HeLa cell migration was suppressed in Cav-1 OE cells while ∆CSD showed increased migration, which corresponded to a decrease in the tight junction protein, zonula occludens (ZO-1). The migration phenotype was confirmed in multiple cancer cell lines. Phosphorylated STAT-3 was decreased in Cav-1 OE cells compared to control and ∆CSD cells; reducing STAT-3 expression alone decreased cell migration. ∆CSD blunted HeLa proliferation by increasing the number of cells in the G2/M phase of the cell cycle. Overexpressing the CSD peptide alone suppressed HeLa cell migration and inhibited pSTAT3. These findings suggest that Cav-1 CSD may be critical in controlling the dynamic phenotype of cancer cells by facilitating the interaction of specific signal transduction pathways, regulating STAT3 and participating in a G2/M checkpoint. Modulating the CSD and targeting specific proteins may offer potential new therapies in the treatment of cancer metastasis.